Antimicrobial efficacy of 0·05% cetylpyridinium chloride mouthrinses - Sreenivasan, P.K.; Haraszthy, V.I.; Zambon, J.J. (Letters in applied microbiology, 2013)
This study evaluated the antimicrobial activity of two commercially available 0·05% cetylpyridinium chloride (CPC) mouthrinses with or without alcohol and examined its antimicrobial activity on oral bacterial species including fresh clinical isolates compared to a chlorhexidine mouthrinse and a control fluoride mouthrinse without CPC. Two different approaches were used to evaluate antimicrobial activity. First, the minimum inhibitory concentration (MIC) was determined for each mouthrinse against a panel of 25 micro‐organisms including species associated with dental caries, gingivitis and periodontitis. Second, supragingival dental plaque obtained from 15 adults was incubated with the four mouthrinses to evaluate antimicrobial activity on micro‐organisms in oral biofilms. Both CPC mouthrinses exhibited lower MIC's, that is, greater antimicrobial activity, against oral Gram‐negative bacteria especially periodontal pathogens and species implicated in halitosis such as Aggregatibacter actinomycemcomitans, Campylobacter rectus, Eikenella corrodens, Porphyromonas gingivalis, Prevotella intermedia and Solobacterium moorei than the control mouthrinse. Ex‐vivo tests on supragingival plaque micro‐organisms demonstrated significantly greater antimicrobial activity by the CPC mouthrinses (>90% killing, P < 0·001) and the chlorhexidine rinse (>98% killing, P < 0·05) compared to the control fluoride mouthrinse. Whilst the chlorhexidine mouthrinse was most effective, mouthrinses containing 0·05% CPC formulated with or without alcohol demonstrated broad‐spectrum antimicrobial activity against both laboratory strains and supragingival plaque bacteria compared to a control mouthrinse without CPC. Significance and Impact of Study These in vitro and ex‐vivo studies provide a biological rationale for previous clinical studies demonstrating the efficacy of CPC mouthrinses in reducing supragingival plaque and plaque‐associated gingivitis. Significance and Impact of Study: These in vitro and ex‐vivo studies provide a biological rationale for previous clinical studies demonstrating the efficacy of CPC mouthrinses in reducing supragingival plaque and plaque‐associated gingivitis.